2011
DOI: 10.3324/haematol.2011.042531
|View full text |Cite
|
Sign up to set email alerts
|

Follicular lymphoma grade 3B is a distinct neoplasm according to cytogenetic and immunohistochemical profiles

Abstract: The online version of this article has a Supplementary Appendix. BackgroundAccording to the current World Health Organization Classification of Lymphoid Tumours, follicular lymphoma is subclassified into three grades according to the number of centroblasts. Follicular lymphoma grade 3 can be further divided into types A and B. Almost all available genetic data on grade 3B follicular lymphomas have been generated from tumors with an additional diffuse large B-cell lymphoma component. The purely follicular type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
100
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 29 publications
12
100
1
5
Order By: Relevance
“…Others have confirmed similar findings. 27 Jaglowski et al, 10 in a SEER review of follicular lymphoma in adolescents and young adults, cite that the relative frequency of low-grade follicular lymphoma increases with age due to the general trend of more aggressive lymphomas in the young population. In patients aged 15-24 years, grades 1 through 3 occur with approximately equal frequencies, whereas in the 35-39 age group, grade 1 represents B55% of diagnoses, followed by grade 2 at 30% and grade 3 at 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Others have confirmed similar findings. 27 Jaglowski et al, 10 in a SEER review of follicular lymphoma in adolescents and young adults, cite that the relative frequency of low-grade follicular lymphoma increases with age due to the general trend of more aggressive lymphomas in the young population. In patients aged 15-24 years, grades 1 through 3 occur with approximately equal frequencies, whereas in the 35-39 age group, grade 1 represents B55% of diagnoses, followed by grade 2 at 30% and grade 3 at 18%.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] According 17,18 representing on average a DHL in 50-60%. 14,[16][17][18][19][20] This also implies that the remaining 40-50% of MYC + lymphomas are "single-hit" and that their importance, despite this high percentage, might have been underappreciated. These lymphomas with MYC translocations, including DHL, have received increased attention because several studies showed them to run an aggressive clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…4 All other lymphomas with a MYC breakpoint, irrespective of the presence of other aberrations, are called "single-hit" lymphomas (SHL). MYC breaks are seen in approximately 10% (3-17%) of all DLBCL and 15-20% of FL grade 3B, 17,18 representing on average a DHL in 50-60%. 14,[16][17][18][19][20] This also implies that the remaining 40-50% of MYC + lymphomas are "single-hit" and that their importance, despite this high percentage, might have been underappreciated.…”
mentioning
confidence: 99%
“…4 BCL6 rearrangement has also been detected in a subset of follicular lymphomas, especially some cases of grade 3 follicular lymphoma and those lacking BCL2 rearrangement. 3,[5][6][7][8][9] Furthermore, BCL6 mutations occur in diffuse large B-cell lymphomas and other types of germinal center or postgerminal center-derived lymphomas; this has been suggested as a mechanism for aberrant BCL6 expression, although the presence of similar changes following somatic hypermutation in benign B cells complicates the interpretation of this finding. 1,[10][11][12][13][14] Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is another B-cell lymphoma of germinal center stage differentiation in which BCL6 translocations have been identified.…”
mentioning
confidence: 67%